Knowledge of Kidney Disease Among Allied Health Sciences Undergraduates: A Cross-Sectional Study in the University of Cape Coast - Victor Obiri Opoku; Theophilus Junior Yankey; Mainprice Akuoko Essuman; George Nkrumah Osei; Tetteh Attoh; Richard K. D. Ephraim (International Journal of Clinical Practice)
Conclusion: This study revealed an adequate knowledge level of KDs and their risk factors among allied health sciences undergraduates. However, an inadequate knowledge of its signs and symptoms was observed indicating a need for improved training.